SEMIOTICS ANALYSIS OF ROLAND BARTHES PUBLIC SERVICE ADVERTISEMENT “VEHICLE TAX RELAXATION FOR THE PROVINCIAL GOVERNMENT OF BALI” - I Made Yuda Suryawan Yuda (ID Solutions, 2021)
This study aims to reveal the moral message conveyed in the public service advertisements of the Bali Provincial Government related to the relaxation of motor vehicle taxes. This study uses a qualitative approach. The data in this study were sourced from the TRIDUTA TV youtube account. This research will then be analyzed using Roland Barthes' semiotic analysis. The results of this study found that in public service advertisements regarding motor vehicle tax relaxation in the province of Bali there are 3 meanings namely connotative meaning, denotative meaning and mythical meaning. The denotation meaning of public service means that the government is socializing the relaxation of motor vehicle taxes. The connotative meaning of the community service is that the motor vehicle relaxation policy is assumed to be a policy that relieves the community and is marked by a